Opportunities for better phosphorus use in agriculture - Masso, C.; Zhang, F.; Adhya, T.K.; Blackwell, M.S.A.; MacIntosh, K.A.; Johnes, P.J.; Haygarth, P.M.; Withers, P.; Feng, G.; Li, H.; Zhang, C.; Wu, J.; et al. (UK Centre for Ecology and Hydrology, 2022)
Low phosphorus use efficiency (~20%) and high phosphorus losses from agricultural land to waterbodies is a growing global problem and exacerbated by climate change and rainfall extremes. Fertiliser use can be optimised and should consider all nutrients. Widespread soil phosphorus testing is required. In some regions appropriate control limits on phosphorus inputs will be needed, whilst in others an increase in P inputs will be required to improve/maintain agricultural productivity. An integrated approach to improve phosphorus use efficiency, reduce losses and increase recycling throughout the food production and consumption chain is needed. A multi-stakeholder approach will, therefore, be critical.